Intra and Inter-Observer Variability in the Measurement of Anterior Chamber Depth Diameter Using B-Mode Ultrasonography - Ghimire, Prasanna; Sah, Brijendra; Barai, Trideep Kumar; Jha, Amit; Paudel, Nabin; Sapkota, Hari (Journal of Nepalgunj Medical College, 2023)
Introduction: B-mode ultrasonography, a non-invasive imaging modality, plays a pivotal role in evaluating ocular structures such as anterior chamber depth. Its measurement is crucial for ocular health assessment and managing conditions like glaucoma cataract and refractive surgery planning. However, ultrasonography's operator-dependent nature impacts diagnostic sensitivity and specificity. Aims: This study investigates intra-observer and inter-observer variability in ultrasonographic ACD measurements and its implications. Methods: A prospective observational study was conducted at Nepalgunj Medical College and Teaching Hospital in September 2023. Healthy volunteers over 17 years of age were enrolled, with ethical approval and informed consent. Ultraso nography was performed using a 7.5 MHz linear transducer, involving a radiologist with over 5 years of experience and a radiology trainee. Reproducibility was assessed using intraclass correlation coefficients (ICC). Results: The study included 150 participants (83 males, 67 females) with a mean age of 25.7 years. ACD demonstrated a linear correlation with age. The mean right ACD was 2.824 mm (range: 2.175 mm - 4.175 mm) and the mean left ACD was 2.826 mm (range: 2.20 mm - 4.175 mm). Age had a significant linear correlation with ACD (p <0.001). Intra-observer variability for both observers showed statistically significant linear correlations (p <0.001), with high Pearson correlation coefficients. Inter-observer variability in mean ACD also exhibited a significant correlation (p<0.01) with excellent agreement. Conclusion: This study highlights the importance of assessing intra and inter-observer variability in ACD measurements by ultrasonography. The findings provide valuable insights for ocular health management, particularly in patients with elevated intraocular pressure. Standardizing measurement techniques can improve diagnostic accuracy and patient care.